Organisational change implementation in a Globalising MNC - Case study on a core IT platform implementation - Pohjasniemi, Essi (My University, 2017)
Digitalisation and globalisation are changing global business environment rapidly. In order to ensure future competitiveness in the rapidly changing business environment, traditional MNCs establish organisational transformation initiatives aiming for increasing their digital capabilities and global efficiency. These major organisational transformations are often organised as projects or portfolios of projects that drive organisational change initiatives. The progress of organisational transformation is dependent on the organisational change implementations’ performance, and for that reason the factors that influence on the success of organisational change implementation in globalising MNCs must be addressed. This thesis studies the factors influencing on the success of organisational change implementation within organisational transformation in a Globalising MNC. The research is conducted as a case study on which qualitative research method is utilised. The subject of this case study is core IT platform implementation in a Globalising MNC. The model formed based on the case study research distinguishes between the four interrelated entities that influence on the success of organisational change implementation within organisational transformation in a Globalising MNC. These entities are organisational transformation (digitalisation and globalisation), drivers of organisational change implementation, the process of leading the organisational change implementation, and the employees’ response to the organisational change implementation. Each of the entities consists of factors that further define the entity’s influence on the success of organisational change implementation. In addition to defining the factors that influence on the success of organisational change implementation, the model discusses on the interrelation of the organisational transformation and organisational change implementation. This thesis research emphasises the change leadership approach in relation to organisational transformation and organisational change implementation literature. As managerial implications the thesis research provides an overview of the factors that influence on the success of organisational change implementation and managerial perceptions on leading the organisational change implementation.
Keywords: Globalising MNC; Organisational Transformation; Organisational Change Implementation; Change Leadership; fi=Master's Degree Programme in International Business|